RARE EARTH MINERALIZATION OF HIGH-PRESSURE SHALES OF THE SITE "RARE-EARTH-EAST-1" (IRTYSH AREA CRUMPLED ZONE) - Portnov, V.; Mussina, E.; Ponomareva, M.; Reva, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Rare earth metals are in high demand in high-tech industries, so the study of their spatial distribution, mineralogy and commercial importance is of the urgent task. A whole new genetic type of rare earth raw materials was detected in Eastern Kazakhstan. In the study of metamorphic rocks Irtysh crumpled zones of the garnet schists, the nucleus of each grain containing phosphate-garnet rare earths, were identified. They relate to cerium and the sodium groups and the main carrier minerals monazite and xenotime contain up to 32% and 42% of cerium and yttrium, respectively. In fact, these rocks are deposits, metamorphosed in the Ordovician period under high and ultra-high pressure. The aim is to explore the Irtysh crumpled zone and study new genetic type of rare earth raw materials in Eastern Kazakhstan, study spatial age and genetic relations; assess its commercial value and development prospects; develop and implement the technological scheme of commercialization of rare earth minerals. The main carrier of the rare-earth mineralization is monazite, which is represented by the free phase in rocks and minerals in garnet-captive mineral. Red and black garnet, as well as its intermediate color forms, identical in composition to captive minerals: monazite (main), titanium and hematite, xenotime, tantalum-niobates (in gneiss-granites) and the complex not yet fully studied rare earth forms in red garnet are identified. Garnet is available in two contrasting forms: red and pink spessartite (with not more than 5% of pyrope) and pyralspite (containing 16-18% of pyrope). Technical tests of rare genetic material of a new type give grounds to consider it to be sufficiently promising for industrial development.
Keywords: facies; raw materials; samples; micro-inclusions; monazite; zircon; isotopic composition; age